Citotoxicidade de cimentos retrobturados experimentais em fibroblastos V79: [recurso eletrônico] - Esteves, Amanda Menon [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
Combining the characteristics of good adhesion and sealing of the AH Plus sealer the biological properties of the MTA, zinc oxide and calcium hydroxide, the purpose of this study was to evaluate the cytotoxicity of these associations. The specimens of the sealers and their associations were mixed and exposure to culture medium (82.4 mm2surface/mL) after the manipulation and incubated in a humidified incubator (37°C and 100% humidity) for 24 h. Chinese hamster lung fibroblasts (V79) were exposed to different dilutions of this extracts for 24 h and cell viability was measured by MTT test. The differences between the cell survival rates were statistically analyzed for Kruskal-Wallis and Dunn (p≤0.05). All sealers showed a significant difference with the group control, except the MTA. Cytotoxicity with the control group increased in the following order: AH Plus < AH Plus + Ca(OH) 2 < AH Plus + OxZn< AH Plus + MTA < MTA (p≤ 0,05). It was concluded that the addition of biological materials in order to improve the consistency of AH Plus for use in retro cavities its toxicity has not decreased significantly

Associando as características de adesividade e bom selamento do cimento AH Plus à ação biológica do MTA, Óxido de Zinco e Hidróxido de Cálcio, a proposta deste estudo foi avaliar a citotoxicidade destas associações. Os espécimes dos cimentos e suas associações foram preparados, e colocados em contato com meio de cultura (82,4 mm2 superfície/mL) logo após a manipulação e deixados em estufa (37°C a 100% umidade) por 24 h. Fibroblastos pulmonares de hamster chinês (V79) foram expostos a diferentes diluições dos cimentos por 24 h e a viabilidade celular foi mensurada pelo teste de MTT. As diferenças entre a taxa de sobrevivência celular foi estatisticamente analisada pelos testes de Kruskal-Wallis e Dunn (p<0,05). Todos os cimentos apresentaram diferença significativa em relação ao grupo controle, com exceção do MTA. A citotoxicidade em relação ao grupo controle cresceu na seguinte ordem: AH Plus < AH Plus + Ca(OH) 2 < AH Plus + OxZn< AH Plus + MTA < MTA (p≤ 0,05). Concluindo-se que o acréscimo de materiais biocompatíveis com o intuito de melhorar a consistência do cimento AH Plus para utilização em retrobturação não diminuiu significantemente sua toxicidade
Keywords: AH Plus; MTA; Ca(OH) 2; Citotoxicidade